An Open Label Phase Ib Dose Escalation Study of TRC105 (Anti‐Endoglin Antibody) with Axitinib in Patients with Metastatic Renal Cell Carcinoma. (6th September 2018) - Choueiri, Toni K.; Michaelson, M. Dror; Posadas, Edwin M.; Sonpavde, Guru P.; McDermott, David F.; Nixon, Andrew B.; Liu, Yingmiao; Yuan, Zhenhua; Seon, Ben K.; Walsh, Meghara; Jivani, Manoj A.; Adams, Bonne J.; et al.
Abstract: Background: TRC105 is an IgG1 endoglin monoclonal antibody that potentiates VEGF inhibitors in preclinical models. We assessed safety, pharmacokinetics, and antitumor activity of TRC105 in combination with axitinib in patients with metastatic renal cell carcinoma (mRCC). Subjects, Materials, and Methods: Heavily pretreated mRCC patients were treated with TRC105 weekly (8 mg/kg and then 10 mg/kg) in combination with axitinib (initially at 5 mg b.i.d. and then escalated per patient tolerance to a maximum of 10 mg b.i.d.) until disease progression or unacceptable toxicity using a standard 3 + 3 phase I design. Results: Eighteen patients (median number of prior therapies = 3) were treated. TRC105 dose escalation proceeded to 10 mg/kg weekly without dose‐limiting toxicity. Adverse event characteristics of each drug were not increased in frequency or severity when the two drugs were administered concurrently. TRC105 and axitinib demonstrated preliminary evidence of activity, including partial responses (PR) by RECIST in 29% of patients, and median progression‐free survival (11.3 months). None of the patients with PR had PR to prior first‐line treatment. Lower baseline levels of osteopontin and higher baseline levels of TGF‐β receptor 3 correlated with overall response rate. Conclusion: TRC105 at 8 and 10 mg/kg weekly was well tolerated in combination with axitinib, with encouraging evidence of activity in patients with mRCC. A multicenter, randomized phase II trial of TRC105 and axitinib has recently completed enrollment (NCT01806064). Implications for Practice: TRC105 is a monoclonal antibody to endoglin (CD105), a receptor densely expressed on proliferating endothelial cells and also on renal cancer stem cells that is implicated as a mediator of resistance to inhibitors of the VEGF pathway. In this Phase I trial, TRC105 combined safely with axitinib at the recommended single agent doses of each drug in patients with renal cell carcinoma. The combination demonstrated durable activity in a VEGF inhibitor‐refractory population and modulated several angiogenic biomarkers. A randomized Phase II trial testing TRC105 in combination with axitinib in clear cell renal cell carcinoma has completed accrual. Abstract : This article reports the results of an open label phase I clinical study that assessed the safety, tolerability, pharmacokinetics, pharmacodynamics, and antitumor activity of TRC105 when given concurrently with axitinib to adult patients with metastatic renal cell carcinoma who progressed following prior treatment with at least one VEGFR TKI.